2001
DOI: 10.1523/jneurosci.21-22-08842.2001
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Endothelin B Receptors in Astrocytes Induces cAMP Response Element-Binding Protein Phosphorylation andc-fosExpression Via Multiple Mitogen-Activated Protein Kinase Signaling Pathways

Abstract: The vasoconstrictor peptide endothelin (ET-1) exerts its physiological and pathological effects via activation of ET(A) and ET(B) receptor (ET-R) subtypes. In this study, we demonstrate that both ET-R subtypes are highly expressed in rat astrocytes in vivo, indicating that these cells are potential targets of the biological effects of ET-1 in the brain. In cultured cortical astrocytes, both ET-R subtypes are expressed, and selective stimulation of ET(B)-R with ET-1 induces phosphorylation of cAMP response elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
77
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 50 publications
11
77
1
1
Order By: Relevance
“…This can be explained by the report that CREB-dependent genes may also be activated by the MAPK and phosphoinositide 3-kinase signaling pathways independent of Ca 2ϩ signaling (57). Likewise, Shaywitz and Greenberg (58) have demonstrated that a variety of kinase signaling pathways can differentially contribute to Ca 2ϩ influx-mediated phosphorylation of CREB in pheochromocytoma (PC12) cells.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the report that CREB-dependent genes may also be activated by the MAPK and phosphoinositide 3-kinase signaling pathways independent of Ca 2ϩ signaling (57). Likewise, Shaywitz and Greenberg (58) have demonstrated that a variety of kinase signaling pathways can differentially contribute to Ca 2ϩ influx-mediated phosphorylation of CREB in pheochromocytoma (PC12) cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that mitogenactivated protein kinase (MAPK) cascades drive the cell cycle through G1, at least in part through modulation of expression of cyclin D1 (Lavoie et al, 1996). Further, it has also been shown that ERKs can affect the expression of CDK inhibitors such as p21 cip1 and p27 kip1 leading to their accumulation and G1 arrest (Kawada et al, 1997;Woods et al, 1997;Schinelli et al, 2001). It is unclear from our results the primary effect of expression of RPS6KA2; whether there is a direct effect on ERK activity or through some negative feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Purified astrocyte cultures were prepared from 20-day-old Sprague-Dawley rat embryos. Cortices were dissected and then mechanically dissociated as described (35). The cultures comprise Ͼ95% GFAP-positive cells (35).…”
Section: Methodsmentioning
confidence: 99%
“…Cortices were dissected and then mechanically dissociated as described (35). The cultures comprise Ͼ95% GFAP-positive cells (35). For detailed information, see Supporting Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation